Fabrication Lecithin Coated Liposomes Containing Guggul Extract for Psoriatic Treatment - Quazi, Rubiya Saher; Quazi, Aamer Iqbal (Journal of Neonatal Surgery, 2025)
Psoriasis is a condition in which up to 78% of patients exhibit a significant association with underlying stress. Numerous herbal nano formulations, such as those incorporating curcumin, aloe vera, and neem, have demonstrated anti-inflammatory and immunomodulatory effects, which may be beneficial in the treatment of psoriasis. Further research is necessary to determine the efficacy and safety of these aspects, along with the ideal dose, treatment duration, and any adverse effects. This study work focuses on the development and assessment of guggul extract-loaded nanoliposomes formulated with sunflower lecithin to enhance the stability and efficacy of the formulation. The study examined different factors, including particle size, zeta potential, entrapment efficiency, in vitro drug loading percentage, and cytokine analysis, indicating that formulation GENL3 is both effective and stable